Діяльність УВКБ ООН із захисту прав біженців в Україні (Серія: Історія. Політологія, 2021)
В статті розглядається діяльність Управління Верховного комісара ООН у справах біженців в Україні на сучасному етапі. Проаналізовано правовий механізм отримання статусу біженця, процедура реадмісії та репатріації в Україні. Розглянуто основні перешкоди у діяльності УВКБ ООН, такі як брак державного фінансування та недосконалість нормативно-правової бази. Визначено пункти тимчасового розміщення для біженців. Проаналізована діяльність УВКБ ООН в умовах пандемії COVID-19. The article considers current main activities of the Office of the United Nations High Commissioner for Refugees in Ukraine. Refugee status is determined in accordance with the Law of Ukraine "On Refugees and Persons in Need of Subsidiary or Temporary Protection", as well as the process of granting this status, their registration and protection. The age, sex and territorial characteristics of refugees in Ukraine are provided, according to the statistics of the State Migration Service. It was also analyzed the legal mechanism of obtaining refugee status and the readmission procedure in Ukraine, which is regulated by state legislation and bilateral agreements.Lack of public funding, low level of staff competence and imperfect legal framework are considered as the main obstacles for UNHCR. It is determined that the repatriation process is a unique phenomenon in Ukrainian realities. It is emphasized that there are not enough temporary accommodation facilities both for refugees (asylum seekers) for foreigners and stateless persons who are illegally staying in Ukraine.The activities of UNHCR in the context of the COVID-19 pandemic are analyzed. Imposed quarantine restrictions are determined as the major difficulty for refugees and asylum seekers, leading to the closure of most countries' borders and impaired access to public services and information. Certain measures taken by Ukraine to protect people UNHCR serves were described. The characteristic of simplification of the procedure for issuing a temporary residence permit in a pandemic is given. The manifestation of UNHCR humanity in the context of the COVID-19 outbreak, when the entire population of the world becomes vulnerable is analyzed. Emphasis is placed on the basic principles of action in such a situation, including access to health care, which should be accessible and inclusive for the whole population without discrimination and xenophobia.It is concluded that the United Nations High Commissioner for Refugees in Ukraine is one of the main humanitarian actors in the field of protection. It is noted that significant changes in the Ukrainian legal framework indicate an improvement in the functioning of the national protection system and are in line with international law.